2023
DOI: 10.1128/spectrum.02324-23
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Enterococcus susceptibility to quaternary ammonium compounds: genes, phenotypes, and the impact of environmental conditions

Ana P. Pereira,
Patrícia Antunes,
Paula Bierge
et al.

Abstract: Quaternary ammonium compounds (QACs) have been extensively used in the community, healthcare facilities, and food chain, in concentrations between 20 and 30,000 mg/L. Enterococcus faecalis and Enterococcus faecium are ubiquitous in these settings and are recognized as nosocomial pathogens worldwide, but QACs’ activity against strains from diverse epidemiological and genomic backgrounds remained largely unexplored. We evaluated the role of Enterococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(50 citation statements)
references
References 81 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, our WGS approach identified a wide range of QAC tolerance genes, underscoring the pressing need for establishing reliable genotypic-phenotypic correlations to elucidate QAC tolerance mechanisms ( Hipólito et al, 2023 ). While several studies have reported that bacterial strains with an elevated MIC or MBC remained susceptible to the in-use BZC concentration ( Vijayakumar et al, 2018 ; Maillard, 2022 ), it is essential to comprehend the environmental factors (e.g., temperature, pH) associated with the expression of these genes ( Gual-de-Torrella et al, 2022 ; Pereira et al, 2023 ) to clarify the environmental, clinical, or veterinary/industrial implications of bacteria with a reduced biocide susceptibility. Further studies are needed to investigate the impact of inappropriate biocide usage or low concentrations, which can act as stressors without killing bacterial pathogens, potentially promoting antimicrobial resistance, and facilitating the transfer of antimicrobial resistance genes ( Maillard, 2022 ; Maillard and Pascoe, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, our WGS approach identified a wide range of QAC tolerance genes, underscoring the pressing need for establishing reliable genotypic-phenotypic correlations to elucidate QAC tolerance mechanisms ( Hipólito et al, 2023 ). While several studies have reported that bacterial strains with an elevated MIC or MBC remained susceptible to the in-use BZC concentration ( Vijayakumar et al, 2018 ; Maillard, 2022 ), it is essential to comprehend the environmental factors (e.g., temperature, pH) associated with the expression of these genes ( Gual-de-Torrella et al, 2022 ; Pereira et al, 2023 ) to clarify the environmental, clinical, or veterinary/industrial implications of bacteria with a reduced biocide susceptibility. Further studies are needed to investigate the impact of inappropriate biocide usage or low concentrations, which can act as stressors without killing bacterial pathogens, potentially promoting antimicrobial resistance, and facilitating the transfer of antimicrobial resistance genes ( Maillard, 2022 ; Maillard and Pascoe, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each experiment was repeated three times and the MIC/MBC values corresponded to the mean of these determinations. To ensure assay reproducibility, the Enterococcus faecalis ATCC 29212 (without any known QACs tolerance genes) was included as a control strain (MIC BZC and MBC BZC varied between 1 and 4 mg/L; Pereira et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each experiment was repeated three times and the MIC/MBC values corresponded to the mean of these determinations. To ensure assay reproducibility, the Enterococcus faecalis ATCC 29212 (without any known QACs tolerance genes) was included as a control strain (MIC BZC and MBC BZC varied between 1-4 mg/L) (Pereira et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, several other factors (e.g., variable temperature or pH, oxygen limitation, starvation, lower or higher bacterial density, bacterial growth phase) that can affect the efficiency of biocides in real application contexts, namely by altering the cytoplasmic membrane or reducing the cell's metabolic activity, are not pondered (Zhang and Rock, 2008;Saito et al, 2014;Ran et al, 2015;Wiegand et al, 2015;Yoon et al, 2015;Gaca and Lemos, 2019;Fox et al, 2022;Maillard and Pascoe, 2024). Recently, we learned that E. faecium and E. faecalis isolates from different epidemiological and clonal backgrounds exhibited decreased susceptibility (MIC and MBC increases of two to eightfold) to BC at 22 • C and/or pH = 5, compared to standard conditions (37 • C; pH = 7.3) (Pereira et al, 2023), confirming the influence of external growth conditions on CBs susceptibility.…”
Section: Biguanidesmentioning
confidence: 99%